Role of salicylic acid pre-treatment on the acclimation of tomato plants to salt- and osmotic stress - Szepesi, Ágnes (Acta Biologica Szegediensis, 2005)
The alleviation of oxidative damage and increased resistance to salt stress and to non-ionic osmotic stress induced by 100 mM NaCl or 100 mOsm polyethylene glycol (PEG) treatments, respectively, often correlate with a more efficient antioxidative defence systems and detoxification mechanisms. Pre-treatment of plants with salicylic acid (SA) enhanced antioxidant enzyme activities in concentration dependent manner and increased the stress tolerance of seedlings. Improved acclimation of SA-pre-treated plants to salt stress depended on the previous activation of the antioxidative enzymes and accumulation of ionic and non-ionic osmolytes, but increased resistance to non-ionic osmotic stress could be achieved in those plants which showed reduced antioxidative enzyme activities at the initial stage of the stress. The present work deals with the possible role of the osmotic adaptation and oxidative defence mechanisms during long-term pre-treatment of tomato plants with low concentrations of SA.